Empowerment of Cepaka Bali Business Group through cultivation and processing of medicinal plants in Kapal Village, Bali - Anak Agung Putu Agung Mediastari; Ni Luh Gede Sudaryati; Anak Agung Komang Suardana; Anak Agung Mas Agung Sri Trisnayanthi; I Gede Mas Agung Darmasaba (Universitas Muhammadiyah Magelang, 2024)
The Community Partnership Program implemented in Cepaka Bali Business Group, Kapal Village, aims to empower local communities through the development of the medicinal plant sector. Through a participatory and collaborative approach, the program integrates intensive training, the application of appropriate technology, and the development of marketing strategies to increase the capacity and competitiveness of local herbal businesses. Results show significant improvements in partners' knowledge and skills related to medicinal plant cultivation and processing, with an average increase of 30-40% on various indicators. The implementation of modern technology in the production process improved efficiency and product quality, while product innovation and digital marketing strategies successfully expanded market reach. Overall, the program increased production capacity by 30% and partners' business income by 35% in six months. This success demonstrates great potential for the development of the medicinal plant sector as a driver of local economic growth and preservation of traditional knowledge in Bali.